Introduction to career education through business and distributive arts for high school fast learners - De Guzman, Rosalinda Cuello (College of Education, University of the Philippines Diliman, 1975)
The purpose of the study was to present some instructional modules designed for the implementation of the objectives of career education through business and distributive arts. The integrated research approach was utilized to answer the following problems: 1) how can the development of human resources, the gifted students specifically, contribute to the attainment of an accelerating rate of economic development and social progress? and 2) what does career education through business and distributive arts offer in relation to such goal? The suggested module clusters provided for learning alternatives in consonance with Piaget's interaction theory of intellectual development. Business and distributive arts are deemed instrumental in introducing career education into the curriculum of the gifted because they provide a wide range of career opportunities and economic literacy which is needed in this age.